Mutualism from the inside: Coordinated development of plant and insect in an active pollinating fig wasp - Jansen González, Sergio (2012)
Recent studies on the obligate interaction between fig trees and their pollinating agaonid wasps have focused on population aspects and wasp–seed exploitation at the level of the inflorescence. Detailed studies on larval and gall development are required to more fully understand how resources are exploited and adaptations fine-tuned by each partner in nursery pollination mutualisms. We studied the larval development of the active pollinating fig wasp, Pegoscapus sp., and the galling process of individual flowers within the figs of its monoecious host, Ficus citrifolia, in Brazil. The pollinator development is strongly dependent on flower pollination. Figs entered by pollenfree wasps were in general more likely to abort. Retained, unpollinated figs had both higher larval mortality and a lower number of wasps. Pegoscapus sp. larvae are adapted to plant development, with two contrasting larval feeding strategies proceeding alongside gall development. The first two larval stages behave as ovary parasites. Later larval stages feed on hypertrophied endosperm. This indicates that a successful galling process relies on endosperm, and also reveals why pollination would be a prerequisite for the production of high-quality galls for this Pegoscapus species.